2018
DOI: 10.1590/s1984-296120180013
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal and external parasitism in the Magellanic Horned Owl Bubo magellanicus (Strigiformes: Strigidae) in Chile

Abstract: To describe the parasitic community of the Magellanic Horned Owl, Bubo magellanicus (Aves, Strigiformes), 19 carcasses from central Chile were analyzed. Ectoparasites were collected through plumage inspection, while endoparasites were collected through traditional techniques of parasitological necropsy. Sixteen owls were infected with at least one species of ectoparasite (84.21%) or endoparasite (31.58%). Eleven of 19 birds (57.89%) harbored feather mites of the three species Pandalura cirrata (42.11%), Glauca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Capillaria falconis ) ( Illescas et al, 1993 ; Sitko and Heneberg, 2019 ), the species identified in our study was C. tenuissima (Rudolphi, 1803). This intestinal Capillaria had been reported also in the American Eagle Owl ( Bubo virginianus ) ( Ramalingam and Samuel, 1978 ) and the Magellanic Owl ( Bubo magellanicus ) ( Grandón-Ojeda et al, 2018 ). The prevalence observed in our study is similar to that detected in Catalonia (57%) by Ferrer et al (2004) , although in this study the sample was lower (only 7 owls) without identifying the species.…”
Section: Discussionsupporting
confidence: 65%
“…Capillaria falconis ) ( Illescas et al, 1993 ; Sitko and Heneberg, 2019 ), the species identified in our study was C. tenuissima (Rudolphi, 1803). This intestinal Capillaria had been reported also in the American Eagle Owl ( Bubo virginianus ) ( Ramalingam and Samuel, 1978 ) and the Magellanic Owl ( Bubo magellanicus ) ( Grandón-Ojeda et al, 2018 ). The prevalence observed in our study is similar to that detected in Catalonia (57%) by Ferrer et al (2004) , although in this study the sample was lower (only 7 owls) without identifying the species.…”
Section: Discussionsupporting
confidence: 65%
“…The acanthocephalan Centrorhynchus parasitizes birds as its main definitive hosts with cockroaches as intermediate, and reptiles, amphibians and rodents as paratenic hosts (Petrochenko, 1958). In Chile, C. spinosus has been recorded on Magellanic-horned owl (Bubo magellanicus) (Grandón-Ojeda et al, 2018). Meanwhile for native carnivores, there is only one record of unidentified acanthocephalans for Chilla fox (Jiménez & Novaro, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Among external arthropods frequently reported in owls [1,2,41,42], K. subpachygaster lice (Table 1; Figure 1: 8) were identified in three out of ten examined tawny owls (S. aluco), while different Kramerella spp. mites (Table 1; Figure 2(7-11)) were identified in almost all positive owls examined.…”
Section: Resultsmentioning
confidence: 99%